Three new species of Pergalumna (Acari, Oribatida, Galumnidae) from Malawi, with updated identification key to known species of the genus from the Afrotropical region - Ermilov, Sergey G.; Starý, Josef (Zootaxa, 2022)
Three new species of Pergalumna (Pergalumna) (Oribatida, Galumnidae)—P. (P.) dedzaensis sp. nov., P. (P.) paratsavoensis sp. nov. and P. (P.) parafrater sp. nov.—are described from sifting litter of highland forests in Central and Southern Malawi. An identification key to known species/subspecies of the genus from the Afrotropical region is presented.